Fetal Supraventricular Tachycardia: Histologic Evidence of Accessory Pathways Due to Incomplete Annulus Fibrosus Formation. (May 2023) - Fritsch, Michael K.; Gotteiner, Nina; Rehman, Jamaal A.; Price, Erica; Ernst, Linda M.
Background: Atrioventricular (AV) reentrant tachycardia is a common type of supraventricular tachycardia (SVT) that occurs in the fetus and neonate. Although many tachycardias resolve within several weeks of birth or respond to medical management, disruptions in the cardiac annulus fibrosus and development of additional accessory pathways may lead to refractory dysrhythmia resulting in fetal hydrops and ultimately, fetal death. Objectives: While accessory pathways have been well documented anatomically in adult and childhood tachyarrhythmias, there are no reports of the histology of these pathways in human fetuses with SVT. Research Design, Subjects, Measures: This is a small case series of 2 fetuses with a history of SVT that resulted in fetal hydrops. Results: In both cases, examination of the cardiac conduction system was unremarkable and examination of the atrioventricular junction revealed a focally thinned and/or discontinuous annulus fibrosus with documented direct continuity between the atrial and ventricular myocardium in 1 case. Conclusions: This case series demonstrates that thinning or absence of the annulus fibrosus is a feature seen in fetal SVT, and the development of subsequent aberrant AV connections due to defective formation of the annulus fibrosus suggests a possible cause for these arrhythmias.